Glycated apolipoprotein A-I assay by combination of affinity chromatography and latex immunoagglutination - Shishino, K; Murase, M; Makino, H; Saheki, S (Annals of clinical biochemistry, 2000)
The degree of glycation of plasma apolipoprotein A-I was measured by a combination of gel filtration, boronate affinity chromatography and latex immunoagglutination. The plasma concentrations of apolipoprotein A-I determined by this combination method (y) correlated well with those determined by turbidimetric immunoassay (x) (y=1.12x + 1.9, r=0.964). The inter- and intra-assay coefficients of variation in the glycated apolipoprotein A-I assay were 4.1-5.0% and 4.0-4.4%, respectively. Interference from plasma glucose at concentrations up to 55.1 mmol/L was eliminated by gel filtration. Labile glycated apolipoprotein A-I did not interfere with the measurement of glycated apolipoprotein A-I. Reference values for glycated apolipoprotein A-I were determined to be 2.4-4.0% (n=140), with no significant difference between men and women. The mean concentration of plasma glycated apolipoprotein A-I in patients with uncontrolled diabetes mellitus (5.11%) was significantly higher than in normal subjects (3.12%, P<0.001). The method is simple, rapid and highly sensitive for determination of the glycation level of plasma apolipoprotein A-I.